Kebijakan Pola Permukiman dan Komposisi Penduduk Area Sub-Das Di Pusat Kota Palembang - Rismayana, Yenni; Nengyanti, Nengyanti; Hartono, Yusuf; Prima, Listen (Universitas Indo Global Mandiri, 2024)
This research aims to analyze settlement patterns spread across several areas in Palembang City, especially in the city center which have been formed based on population composition in the upstream, transitional and downstream watersheds. The city of Palembang is in a lowland area, formed on a swamp with many tributaries from the main river that divides the city, namely the Musi River. The Musi River divides Palembang City into 2 regions, namely Upstream (Seberang Ulu) and Downstream (Seberang Ilir). The tributaries are divided geographically according to the area, there are 15 tributaries upstream and 9 tributaries downstream. Since the river was formed, the residents of this city have lived along the watershed by building residences both periodically and permanently. This longitudinal pattern downstream of the sub-watershed empties into the Musi River. Apart from the longitudinal pattern, a random/scattered pattern is also formed to fill empty land between settlements along the watershed. Another pattern that is further away from the watershed is a centralized pattern where the buildings are neatly and orderly designed. The composition of the population living in these settlement patterns is important to research because it is an indicator of sustainable development. The composition includes demographic characteristics, social status with stratification therein, economic stratification, population distribution both geographically and administratively and surviving culture. These five characteristics can determine the type of housing being built and describe the level of community welfare.